2011
DOI: 10.1097/prs.0b013e3181fad3a7
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Institution Experience of Hand Surgery Litigation in a Major Replantation Center

Abstract: The majority of the patients who filed claims did so because of the decision not to replant. Only 2.98 percent (five of 168) of all attempted revascularization/replantation patients filed claims against the authors' institution; all claims were notably dropped. The legal system appears to support physicians and institutions that treat these complex injuries. Better patient understanding of the decision-making process and complications involving treatment of traumatic hand injuries may decrease the number of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A clean-cut "guillotine"-type amputation with minimal vascular injuries, a short duration of ischemia, and a correct conservation of the amputated part are the main prognostic factors for successful reimplantation surgery. [17][18][19] For our patient, since none of these conditions was present, the orthopedic surgeon considered reimplantation to be impossible. Although brain penetrating injuries are less common than brain closed injuries in the civilian population, they are far more lethal.…”
Section: Discussionmentioning
confidence: 93%
“…A clean-cut "guillotine"-type amputation with minimal vascular injuries, a short duration of ischemia, and a correct conservation of the amputated part are the main prognostic factors for successful reimplantation surgery. [17][18][19] For our patient, since none of these conditions was present, the orthopedic surgeon considered reimplantation to be impossible. Although brain penetrating injuries are less common than brain closed injuries in the civilian population, they are far more lethal.…”
Section: Discussionmentioning
confidence: 93%
“…9 Bastidas et al highlight the importance of patient communication in their review of amputation-related litigation at their institution. 10 Early surgical management of the severely injured limb should follow 3 basic tenets: thorough sharp debridement of contaminated tissue, retention of all viable tissue for subsequent reconstruction or amputation coverage, and maintaining the highest potential for patient function with or without a prosthesis. 11 The initial focus is often on the bony injury, yet the status and handling of soft tissues are often the best predictors of limb length and final closure 9 (Fig.…”
Section: Initial Wound Managementmentioning
confidence: 99%
“…There is a discrepancy, however, between malpractice claim results based upon the perceived complexity of the procedure (9). Bastidas et al published their single-institution experience of hand surgery litigation at a major replantation center in New York (15). In their study of claims related to traumatic hand injuries over an 8-year period, only 1 of 23 patients received a successful settlement (15).…”
Section: Legal and Financial Consequences Of Medical Errorsmentioning
confidence: 99%
“…Bastidas et al published their single-institution experience of hand surgery litigation at a major replantation center in New York (15). In their study of claims related to traumatic hand injuries over an 8-year period, only 1 of 23 patients received a successful settlement (15). They concluded that the legal system generally supports physicians and institution that treat complex injuries.…”
Section: Legal and Financial Consequences Of Medical Errorsmentioning
confidence: 99%